Knowledge, attitudes, and practices towards Human Papilloma Virus and uptake of HPV vaccine: A protocol for a systematic review. - Naharin Sultana Anni; Nadia Rehman; Agatha Nyambi; Anthony Musiwa; Tatyana Graham; Roseline Dzekem Dine; Maya Stevens-Uninsky; Elizabeth Alvarez; Zain Chagla; Laura Banfield; Lawrence Mbuagbaw (PLoS ONE)
Background Despite a high burden of Human Papilloma Virus (HPV)-associated diseases, HPV vaccine uptake is disparate globally. The objective of this systematic review is to summarize the existing evidence on knowledge, attitudes, and practices (KAP) regarding HPV and the uptake of the HPV vaccine. Methods and analysis We will conduct a systematic review of observational studies that report data on HPV KAP and vaccine uptake among people aged 16 and above. We will search MEDLINE, CINAHL, Embase, Emcare, Web of Science, Cochrane Library, Global Health, and PsycInfo. We will conduct screening, data extraction, and assessment of the methodological quality of the included studies in duplicate. A random-effects model will be used to pool data. Subgroup analysis will be done for age younger adults (≤ 26 years old) and older adults (> 26 years old), sex (men and women), income level (as per World Bank), and WHO region. This systematic review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PROSPERO registration number for the review is CRD42024532230. Ethics and dissemination Ethical approval is not necessary as this study will review secondary published data. Our findings will be disseminated as part of a doctoral thesis and through peer-reviewed journal publications and conferences.